(untitled) - Parkin, Michael (Reading, Mass., 1994)
This text is the microeconomics section from the second edition of Parkin & King's "Economics". It includes a range of applications of demand and supply theory as well as aspects of oligopoly and game theory.
Keywords: Microeconomics,Kinh tế vi mô